Ecoprint Preneur Melalui Sinergi Kreativitas, Tata Kelola Usaha, dan Legalitas Produk Ramah Lingkungan di Kampung Legok, Kelurahan Bajubang, Kabupaten Batanghari - Sukatin; Dinda Aulia; Reza Amanda; Siti Nurhikmah; Ulil Absor; Zidan Asror; Rian Hidayat; Irawan Setiawan (PT. Hasba Edukasi Mandiri, 2026)
The Ecoprint Entrepreneur Program: Synergy of Creativity, Business Management, and Legality of Environmentally Friendly Products is a community service activity that aims to improve the skills, creativity, and understanding of the community in developing creative businesses based on environmentally friendly ecoprinting. This activity was carried out through workshops that included presentations on the basic concepts of ecoprint, awareness of environmentally friendly products, an introduction to business management and product legality, as well as hands-on practice in making ecoprints on fabric and tote bags. The participants were women from the community who had the potential to develop home-based businesses. The results of the activity showed an increase in participants' knowledge and skills in ecoprint techniques, marked by their ability to produce ecoprint products with varied leaf motifs and aesthetic value. In addition, this activity also encouraged a change in the participants' mindset in seeing ecoprint as a business opportunity that can be developed sustainably. The synergy between creativity, understanding of business management, and awareness of product legality is the initial capital in building a competitive ecoprint business that supports environmental preservation and strengthens the local economy.